Draft Annual Plan 1978-79 Government of West Bengal - Planning Commission (Planning Commission, 1977)
The principal reason for the low crop intensities in the State is the paucity of irrigation facilities during the non-monsoon months. The land is generally left fallow during the winter months though with irrigation water it could be utilised for growing a second crop. For increasing agricultural production through multiple cropping the provision of perennial irrigation system is essential by utilising immense surface water resources of the State which are either being wasted flowing down ultimately to the sea or creating additional problem of drainage congestion and flooding in some areas. The state has all other natural resources such as water, fertile land and man power required for growing good food crops.
Irrigation and Waterways Directorate, Government of West Bengal